Review on Automotive Power Generation System on Plug-in Hybrid Electric Vehicles & Electric Vehicles - Yap, Wee Leong; A. R., Razali; Priyandoko, Gigih; Nazrul Idzham, Kasim (EDP Sciences, 2016)
Regenerative braking is a function to recharge power bank on the Plug-in electric vehicles (PHEV) and electric vehicles (EV). The weakness of this system is, it can only perform its function when the vehicle is slowing down or by stepping the brake foot pedal. In other words, the electricity recharging system is inconsistent, non-continuous and geography dependent. To overcome the weakness of the regenerative braking system, it is suggested that to apply another generator which is going to be parallel with the regenerative braking system so that continuous charging can be achieved. Since the ironless electricity generator has a less counter electromotive force (CEMF) comparing to an ironcored electricity generator and no cogging torque. Applying the ironless electricity generator parallel to the regenerative braking system is seen one of the options which creates sustainable charging system compared to cored electricity generator.